Gap detection of bus stops using GIS/GPS - Bachok, Syahriah; Adumi, Mohd Izul Fikri; Mohamed Osman, Mariana (American Scientific Publishers, 2017)
A research on bus stop gap detection is presented in this paper. Planning and development of bus stops required various considerations. Land availability, landuse, catchment, route matching, infrastructure fitting, barrier free and micro-climate friendly design are some of the factors heeded prior to such installations. These are important to ensure optimal accessibility, connectivity and coverage for users as well as maintaining operational sustain ability for services providers. This paper reports the findings of research undertaken on selected bus routes in Ipoh, the capital city of Perak, a state in Peninsula Malaysia. Deviation between designated and actual stopping points of buses has been identified. Passengers have been recorded to have embarked and disembarked within a range 2 to 1116 meters from the designated stops. Additionally, these gaps have been captured manually on-board, using GIS/GPS apparatus, analysed descriptively and presented to the bus operators, for purposes of future improvement of their service provision. Among factors contributing to the gaps were driver’s behaviour, non-compliance with standard operating procedures and the mismatch between origin/destination of passengers’ and planned locations of bus stops. It has been suggested that with the current absence of such system to monitor bus performance, operators might take up on the installation of GPS/GIS equipment on board; introduce, implement and enforce driver’s ethics codes and revise some bus stop locations currently inappropriately serving the existing and potential patrons. For benefits of marginalised groups of users, ‘request stops’ system and ‘ladies only section’ can also be applied to some bus routes, in view of ensuring additional safety and security elements.